Enhanced thermal and mechanical properties of flame-retardant expandable graphite modified silk fibroin-based rigid polyurethane foam - Xu Zhang; Qihong Guan; Qikai Xiao; Zhi Wang; Hua Xie (Case Studies in Thermal Engineering)
At present, in order to reduce the environmental pollution caused by the use of petrochemical products, the preparation of flame-retardant polyurethane foam (PUF) using green raw materials is increasingly attracting widespread attention. A biomass protein-based green flame-retardant rigid PUF (RPUF) with expandable graphite (EG) and silk fibroin (SF) was prepared in a one-step process. Thermal stability, combustion characteristics and compression properties of modified RPUFs were investigated by thermogravimetric analysis, cone test, limiting oxygen index (LOI) test, UL-94 vertical burning test and mechanical compression test. The RPUF with 10 wt% EG (RPUF-SF/EG10) exhibited superior heat resistance, with the highest initial decomposition temperature (Ti), integral programmed decomposition temperatures (IPDT) and activation energy (E). And RPUF-SF/EG10 had the lowest peak heat release rate (PHRR) and total heat release (THR), and it also showed the highest LOI and had a flammability rating of V-0. In Addition, the apparent density and compressive strength of RPUF-SF/EG10 were the largest among the four EG-added materials. The results indicated that RPUF-SF/EG10 had excellent thermal stability, flame retardancy and compression resistance, which was attributed to the synergistic effect of SF and EG in the system. This provided a valuable reference for the development of new, environmentally friendly and high-performance RPUFs.